Global and Arctic effective radiative forcing of anthropogenic gases and aerosols in MRI-ESM2.0 - Oshima, Naga; Yukimoto, Seiji; Deushi, Makoto; Koshiro, Tsuyoshi; Kawai, Hideaki; Tanaka, Taichu Y.; Yoshida, Kohei (Progress in earth and planetary science, 2020)
The effective radiative forcing (ERF) of anthropogenic gases and aerosols under present-day conditions relative to preindustrial conditions is estimated using the Meteorological Research Institute Earth System Model version 2.0 (MRI-ESM2.0) as part of the Radiative Forcing Model Intercomparison Project (RFMIP) and Aerosol and Chemistry Model Intercomparison Project (AerChemMIP), endorsed by the sixth phase of the Coupled Model Intercomparison Project (CMIP6). The global mean total anthropogenic net ERF estimate at the top of the atmosphere is 1.96 W m −2 and is composed primarily of positive forcings due to carbon dioxide (1.85 W m −2 ), methane (0.71 W m −2 ), and halocarbons (0.30 W m −2 ) and negative forcing due to the total aerosols (− 1.22 W m −2 ). The total aerosol ERF consists of 23% from aerosol-radiation interactions (− 0.32 W m −2 ), 71% from aerosol-cloud interactions (− 0.98 W m −2 ), and slightly from surface albedo changes caused by aerosols (0.08 W m −2 ). The ERFs due to aerosol-radiation interactions consist of opposing contributions from light-absorbing black carbon (BC) (0.25 W m −2 ) and from light-scattering sulfate (− 0.48 W m −2 ) and organic aerosols (− 0.07 W m −2 ) and are pronounced over emission source regions. The ERFs due to aerosol-cloud interactions (ERFaci) are prominent over the source and downwind regions, caused by increases in the number concentrations of cloud condensation nuclei and cloud droplets in low-level clouds. Concurrently, increases in the number concentration of ice crystals in high-level clouds (temperatures < –38 °C), primarily induced by anthropogenic BC aerosols, particularly over tropical convective regions, cause both substantial negative shortwave and positive longwave ERFaci values in MRI-ESM2.0. These distinct forcings largely cancel each other; however, significant longwave radiative heating of the atmosphere caused by high-level ice clouds suggests the importance of further studies on the interactions of aerosols with ice clouds. Total anthropogenic net ERFs are almost entirely positive over the Arctic due to contributions from the surface albedo reductions caused by BC. In the Arctic, BC provides the second largest contribution to the positive ERFs after carbon dioxide, suggesting a possible important role of BC in Arctic surface warming.